Patient-reported assessment of compassion in Spanish: a systematic review - Soto-Rubio, Ana; Picazo, Carmen; Gil-Juliá, Beatriz; Andreu-Vaillo, Yolanda; Pérez-Marín, Marian; Sinclair, Shane (Frontiers in Medicine, 2024)
Aims and objectives This systematic review aims to: (1) explore which tools have been used in Spanish to measure compassion; (2) know which of these tools could be used to assess compassion in healthcare settings from the perspective of patients; (3) evaluate the quality of these patient-reported measures in Spanish contexts; and (4) determine which of these instruments would be best suited to be used in healthcare settings. Background Compassion has been recognized as a fundamental dimension of quality healthcare. Methods Several scientific databases were consulted for relevant records published up to December 16th, 2021. In accordance with PRISMA guidelines, 64 studies were included. Results and conclusions while existing instruments, validated in Spanish, allow for the measurement of self-compassion or compassion to others, there are no valid and reliable measures currently available in Spanish to measure patient-reported compassion. Relevance to clinical practice In order to ensure and promote compassion in the health care context, it is essential to have a valid and reliable tool to measure this construct in a patient-informed way, and this is currently not possible in the Spanish-speaking context because of the lack of such an instrument in Spanish.